(untitled) (The Pakistan Development Review, 1988)
Analytical efforts to understand the factors which influence population growth and the variables which affect fertility behaviour have become the concern of most social scientists. Studies done to look at the interrelationship between population growth and economic development have mostly used the viewpoints of economics and demography. The economists belonging to different schools of thought have treated the population question differently: while some of them have treated population growth as an exogenous variable, others have considered it to be endogenous. The economist’s decision-making model of fertility behaviour, which considered children as an economic good, was developed as an extension of the conceptual framework of the micro-economic model of a consumer’s decision-making process in allocating a restricted budget to alternative uses. The validity of the application of an economic theoretical framework to household fertility behaviour has, however, been questioned by many social scientists.